(untitled) (Journal of Computational Mathematics, 2018)
In this paper we obtain a Hoffman-Wielandt type theorem and a Bauer-Fike type theorem for singular pencils of matrics. These results delineate the relations between the perturbation of the eigenvalues of a singular diagonalizable pencil A-λB and the variation of the orthogonal projection onto the column space R ( matrix A^H B^H matrix ).